Differences in attention attributes for female handball players - Gillard, M.; Romenskaya, O. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The article shows the differences in the attention properties of handball players of different game positions. Two of the important properties of attention such as volume and concentration (intensity) were studied both for each individual handball player and groups of players of different positions. The data obtained allow us to determine the directions for further improving of handball players and help to form the most suitable bundles of players for the quality of game interaction.